Otras iniciativas de investigación y publicación de la Facultad de Ciencias Sociales y Humanas de la Universidad de Antioquia (2002)
ABSTRACT: This brief text aims to show some investigation and publishing initiatives existing research within the Faculty of Social and Human Sciences at the University of Antioquia.